STAKEHOLDER-INTEGRATED APPROACH TO ASSESSMENT OF LEVEL IN URBAN ENGINEERING AND INFRASTRUCTURE PROVISION - K. A. Mamonov; S. G. Nesterenko; E. S. Shterndok; M. A. Grek; A. V. Rudomakha (Наука и техника)
An algorithm for assessment of level in engineering and infrastructure support of urban area has been developed while using geographic information systems (GIS) in the framework of stakeholder-integrated approach. In order to achieve the target goal the following tasks have been solved: description of stakeholder-integrated approach to assessment of level in engineering and infrastructure support of cities; systematization of the existing approaches to assessment of level in engineering and infrastructure support of cities; development of an algorithm for determination of data for spatial models; development of spatial models for assessment of level in engineering and infrastructure support while using geographic information systems. A comprehensive approach has been proposed to simulate spatial factors in order to assess urban engineering and infrastructure support, which is different from the existing ones due to development and application of GIS tools. Spatial models of urban engineering and infrastructure support have been developed in the paper. They include territorial, ecological, power engineering, socio-economic and other characteristics. These models have made it possible to implement the proposed approach for simulation of the spatial factors. It is necessary to point out the fact that geographic information systems have been used and this approach provides a possibility to detailed consideration of models which reveal influence of spatial factors. So it is possible to increase objectivity of solving the problem.